Hair [videorecording (DVD)] - Forman, Miloš; Savage, John, 1949-; Williams, Treat; D'Angelo, Beverly; Golden, Annie; Moore, Melba; Ragni, Gerome (MGM Home Entertainment, 1999)
Fresh from the farm, Claude Bukowski arrives in New York City for a date with the Army Induction Board, only to walk into a hippie "happening" in Central Park and fall in love with the beautiful Sheila. Befriended by the hippies' pacifist leader, Berger, and urged to crash a formal party in order to declare his love for Sheila, Claude begins an adventure that lands him in jail, Central Park Lake and finally, in the army. But Berger's final effort to save Claude from Vietnam sets in motion a bizarre twist of fate ... with shocking consequences.